Protocol for a non-randomised feasibility study evaluating a codesigned patient safety guide in primary care. Issue 1 (20th January 2021) - Morris, Rebecca L; Gallacher, Kay; Hann, Mark; Rolfe, Carly; Small, Nicola; Giles, Sally J; Sanders, Caroline; Campbell, Stephen M
Abstract : Introduction: Patients and carers should be active partners in patient safety with healthcare professionals and be empowered to use personalised approaches to identify safety concerns and work together to prevent them. This protocol paper details a study to examine the feasibility of a multicomponent intervention to involve patients and/or carers in patient safety in primary care in the UK. Methods and analysis: This is a two-phase, non-randomised feasibility mixed methods pragmatic study of a patient safety guide for primary care (PSG-PC). 8 general practices will recruit 120 patient and/or carer participants. All patient and/or carer participants will receive the PSG-PC. It will examine the feasibility and acceptability of the PSG-PC in primary care settings in patients aged 18 years or older who attend appointments at general practice with health professionals four or more times per year as either patients or carers. It will identify secondary outcomes for improving patient safety, health status and patient empowerment, and reducing health service utilisation over 6 months between baseline and 6-month follow-ups. The findings will inform whether a main effectiveness trial is feasible and, if so, how it should be designed, and how many patients and practices will be needed. The study will be undertaken between January 2020 and September 2021. Ethics and dissemination: Ethical approval was obtained from the National Health Service London-West London and Gene Therapy Advisory Committee Research Ethics Committee (reference: 19/LO/1289). Research findings will be disseminated with participating general practices and shared in a range of different ways to engage different audiences, including presenting at international and national conferences, publishing in open-access, peer-reviewed journals and facilitating dissemination workshops within local communities with patients, carers and healthcare professionals. Trial registration number: ISRCTN90222092 .